2015
DOI: 10.1088/0268-1242/30/2/024006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent thermal conductivity in Mg-doped and undopedβ-Ga2O3bulk-crystals

Abstract: Abstract. For β-Ga 2 O 3 only little information exist concerning the thermal properties, especially the thermal conductivity λ. Here, the thermal conductivity is measured by applying the electrical 3ω-method on Czochralski-grown β-Ga 2 O 3 bulk crystals, which have a thickness of 200 µm and 800 µm. At room temperature the thermal conductivity along the [100]-direction in Mg-doped electrical insulating and undoped semiconducting β-Ga 2 O 3 is confirmed as 13 ± 1 Wm −1 K −1 for both crystals. The thermal conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 19 publications
5
46
1
1
Order By: Relevance
“…This thermal conductivity is slightly lower than a previous measurement of the thermal conductivity of bulk, single crystalline b-Ga 2 O 3 ($13 W m À1 K À1 -black dotted line in Fig. 6), 49,50 and roughly half the value of the thermal conductivity of typical GaN HFET component AlGaN (16.6 W m À1 K À1 ). 51 Given the polycrystalline nature of our b-Ga 2 O 3 films, this reduction in thermal conductivity relative to the single crystalline value reported in Ref.…”
Section: -6contrasting
confidence: 55%
“…This thermal conductivity is slightly lower than a previous measurement of the thermal conductivity of bulk, single crystalline b-Ga 2 O 3 ($13 W m À1 K À1 -black dotted line in Fig. 6), 49,50 and roughly half the value of the thermal conductivity of typical GaN HFET component AlGaN (16.6 W m À1 K À1 ). 51 Given the polycrystalline nature of our b-Ga 2 O 3 films, this reduction in thermal conductivity relative to the single crystalline value reported in Ref.…”
Section: -6contrasting
confidence: 55%
“…9 Thermal conductivities of β-Ga2O3 along some highly symmetric directions have been reported previously by several authors. [10][11][12] For example, Guo et al 10 They observed a ~1/T dependence on the thermal conductivity for all the measured directions at temperatures >200 K and a 1/T 3 -1/T 4 dependence at temperatures <200 K. Handwerg et al 11 reported the thermal conductivity of Mg-doped and undoped β-Ga2O3 bulk crystals along the [100] direction from 4 to 300 K measured using the 3ω method. Galazka et al 12 also measured the thermal conductivity of β-Ga2O3 along the [010] direction using the laser flash method and reported a value of 21 W m -1 K -1 at room temperature.…”
Section: Textmentioning
confidence: 99%
“…directions from the current measurements over the temperature range from 80 to 400 K (solid symbols), with the literature measurements [10][11][12] (open symbols) included for comparison. It is interesting to note that although the current measurements agree well with the measurements by Guo et al 10 at high temperatures >200 K for both directions, the measurements by Guo et al 10 at low temperatures <200 K are significantly higher than the current measurements.…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[10]). An exemplary measurement of ∆T (f ) ∝ U 2ω (f ) is shown in figure 4 together with a fit using equation 6 shown in figure 6.…”
Section: Resultsmentioning
confidence: 99%